The Influence of Smart Tourism Technology (STT) on Intention to Visit in Talaud Island Regency - Deborah Naomi Tampoli; Florentina Kurniasari; Johny Natu Prihanto (Conference Series, 2020)
Technological sophistication provides a lot of ease of access information, including tourism information. Usually, before makes a travel itinerary, tourists often look for more information before making a decision. The objective of this research is to find out the effect of smart tourism technology application into the intention to visit in Talaud Island Regency through trustworthiness. This research has six hypotheses and is measured quantitatively by distributing questionnaires to 130 respondents. All the data collection is further analyzed with a structural equation modeling method. The results of this research found that information quality, source credibility¸ and accessibility are positive influences. On the contrary, interactivity and personalization do not significantly affect trustworthiness. In addition, trustworthy people have a positive effect on their intention to visit. The finding of this research also indicates that information which was received by the tourist would increase their confidence and encourage them to stay.